Experimental research of retreatability of root canals filled with bioceramic sealer - A. V. Mitronin; D. A. Ostanina; Yu. A. Mitronin (LLC "Endo Press", 2021)
Aim. This study aimed to determine the residual filling material and the reestablishment of working length and apical patency after retreatment of TotalFill® BC Sealer.Materials and methods. Thirty maxillary incisors were used in a single cone obturation technique with TotalFill BC Sealer (FKG, Switzerland) and randomly divided into 6 groups according to the retreatment technique. The samples were scanned by micro-CT before and after retreatment in order to evaluate the residual filling material on the root dentin walls. Data were analyzed statistically with the Kruskal-Wallis tests (p < 0.05).Results. No instrumental protocol was able to remove all obturation material from the root canals. The differences in reduction in the total volume of filling material percentage were statistically significant (p < 0.05) among groups with and without ultrasound or sound activation in retreatment protocol.Conclusions. The most effective root canal retreatment was determined with D-Race + XP-endo Shaper + XP-Endo Finisher R + US (3.0 W) protocol; it was found that the efficiency of filling material removal was more than 92%.